2018
DOI: 10.1002/adma.201804074
|View full text |Cite
|
Sign up to set email alerts
|

Vertex‐Type Engineering of Pt–Cu–Rh Heterogeneous Nanocages for Highly Efficient Ethanol Electrooxidation

Abstract: Mastery over the architecture and elemental distribution of metal nanocrystals at the nanoscale can effectively tailor and improve their catalytic properties. Herein, the vertex‐type‐selective growth of metallic nanohorns on a central nanocrystal is constructed via a one‐pot solvothermal synthesis, despite the fact that the site‐selective epitaxy of the second phase proceeds on all the vertices of the seeds. The prepared vertex‐type‐selective Pt–Cu–Rh heterogeneous nanocages (HNCs) are composed of a Rh‐decorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…All of the aforementioned catalysts showed a high activity toward EOR with peak currents several times higher than that obtained on a commercial catalyst of the equivalent metal supported on carbon. One of the most interesting contributions was developed by Wang et al., who synthesized Pt−Cu−Rh nanocages containing abundant stepped atoms and various high‐index facets around the surface . Electrochemical tests showed that Pt−Cu−Rh HNCs exhibited an outstanding activity (peak current of 7300 A/cm −2 ) attributed to the synergistic effect between Pt, Cu, and Rh components, its high specific surface area, as well as abundant concave/convex sites and the various high‐index facets around the surface.…”
Section: Shape‐controlled Metal Nanoparticles For the Eormentioning
confidence: 99%
“…All of the aforementioned catalysts showed a high activity toward EOR with peak currents several times higher than that obtained on a commercial catalyst of the equivalent metal supported on carbon. One of the most interesting contributions was developed by Wang et al., who synthesized Pt−Cu−Rh nanocages containing abundant stepped atoms and various high‐index facets around the surface . Electrochemical tests showed that Pt−Cu−Rh HNCs exhibited an outstanding activity (peak current of 7300 A/cm −2 ) attributed to the synergistic effect between Pt, Cu, and Rh components, its high specific surface area, as well as abundant concave/convex sites and the various high‐index facets around the surface.…”
Section: Shape‐controlled Metal Nanoparticles For the Eormentioning
confidence: 99%
“…Fuel cells are promising renewable energy devices for advanced portable electronic devices and electrical vehicles. [ 1,2 ] They can convert chemical energy into electrical power via the electrocatalytic processes including the methanol oxidation reaction (MOR), [ 3 ] ethanol oxidation reaction, [ 4 ] oxygen reduction reaction (ORR), [ 5 ] hydrogen oxidation reaction (HOR), [ 6 ] etc. To date, platinum (Pt) is still considered as the most promising and commonly used electrocatalyst in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…To date, platinum (Pt) is still considered as the most promising and commonly used electrocatalyst in fuel cells. [ 1–6 ] However, the insufficient activity, inadequate durability, and the high cost and scarcity of Pt hinder the practical large‐scale commercialization of fuel cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations